2013
DOI: 10.1002/jgrd.50368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monsoon system on α‐HCH fate in Asia: A model study from 1948 to 2008

Abstract: The Chinese Gridded Pesticide Emission and Residue Model was applied to simulate long‐term environmental fate of α‐hexachlorocyclohexane (HCH) in Asia spanning 1948 to 2008. The simulation identifies the southern Tibetan Plateau and the margin of the Asian monsoon regime from the northeast area of the Tibetan Plateau to the Northeast China as sink areas. This spatial pattern of sink distribution is closely related to the summer monsoon activities in Asia. Wet deposition associated with the summer monsoon (June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…However, Indian sources only made a minor contribution to human risk of cancer in China (Xu et al, 2013a). Recently, Xu et al (2013b) studied the environmental fate of α-HCH in Asia during the period 1948 to 2008, using the Chinese Griddled Pesticides Emission and Residue Model (ChnGPERM) simulation model. They found that the environmental fate of a-HCH in the Southern TP was influenced by the atmospheric outflow from Indian sources; whist sources in China played a major role for its accumulation in eastern TP.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 99%
“…However, Indian sources only made a minor contribution to human risk of cancer in China (Xu et al, 2013a). Recently, Xu et al (2013b) studied the environmental fate of α-HCH in Asia during the period 1948 to 2008, using the Chinese Griddled Pesticides Emission and Residue Model (ChnGPERM) simulation model. They found that the environmental fate of a-HCH in the Southern TP was influenced by the atmospheric outflow from Indian sources; whist sources in China played a major role for its accumulation in eastern TP.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 99%
“…31−33 With the influence of high temperatures and the outbreak of monsoons, these POPs can transport to the remote areas. 34 Despite the large production and usage of CPs in the South Asia region, the study of CP in this area is still limited. There is an urgent need for more studies on the environmental levels of CPs in this continent, particularly the countries with large production and usage, especially China and India.…”
mentioning
confidence: 99%
“…S3), which is certainly influenced by the emission distribution (maximum in northern India, in the Indo-Gangetic Plain) as well as the direction of advection in air (prevailing westerly, with northerly component). For α-HCH, this gradient was also reflected in soil distributions in India, which were based on a gridded mass balance model (Xu et al, 2013). While PCB28 had net volatilisation after a few years Figure 3.…”
Section: Multidecadal Air-surface Cycling Of Pops and Historic Trendsmentioning
confidence: 95%